Pengaruh Komitmen Manajemen, Kemampuan Teknik Personal Dan Information Technology Sophistication Pada Kinerja Sistem Informasi Akuntansi - Swara, Luh Gede Ira Pratiwi; Widhiyani, Ni Luh Sari (E-Jurnal Akuntansi; Vol 28 No 1 (2019), 2019)
This study aims to empirically the effect of management commitment, personal technical skills and information technology sophistication on the performance of accounting information systems in rural banks in Badung Regency. The population of this study was 52 rural banks in Badung Regency. Sampling used saturated sample technique or census, where the entire study population will used samples, so that the samples used as many as 52 BPR. Respondents in this study then selected 3 people in each BPR. Data analysis technique used multiple linear regression analysis. The results show that: 1) management commitment has positive and significant effect on the performance of BPR accounting information systems in Badung Regency, 2) personal engineering skills have positive and significant effect on the performance of BPR accounting information systems in Badung Regency and 3) information technology sophistication positive and significant effect on the performance of the BPR accounting information system in Badung Regency. Keywords: Management commitment, personal technical ability, IT sophistication, SIA performance.